2012
DOI: 10.1111/cdoe.12017
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism and associated factors among Dutch adolescents

Abstract: Sleep bruxism and awake bruxism are common conditions among Dutch adolescents, with self-reported prevalence rates that are slightly higher than those derived from most large-scale studies on adults. Several predictor variables were found to be exclusively associated with either form of bruxism, corroborating the common suggestion that both circadian manifestations are, at least in part, different entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
135
2
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(173 citation statements)
references
References 40 publications
13
135
2
16
Order By: Relevance
“…10 Moreover, sleep and awake self-reports still remain the most suitable approach to gathering data for large samples. 9,14 However, a large scale polysomnographic study showed that there is an overestimation of the sleep bruxism diagnostic when made with a self-report. 28 Although the self-report of sleep bruxism, awake bruxism and parafunctional habits has low specificity, the testretest reliability revealed that the questions could be considered reliable for use in this study, even though the question on parafunctional habits may have been hard to interpret, because of the variety of aspects involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Moreover, sleep and awake self-reports still remain the most suitable approach to gathering data for large samples. 9,14 However, a large scale polysomnographic study showed that there is an overestimation of the sleep bruxism diagnostic when made with a self-report. 28 Although the self-report of sleep bruxism, awake bruxism and parafunctional habits has low specificity, the testretest reliability revealed that the questions could be considered reliable for use in this study, even though the question on parafunctional habits may have been hard to interpret, because of the variety of aspects involved.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Among the factors involved in painful TMD pathogenesis, the role of sleep bruxism, awake bruxism, and parafunctional habits has been studied extensively in the adult population, 6 whereas there are few studies on this issue in the pediatric population. 7,8,9 In regard to sleep bruxism and awake bruxism, a recent international expert consensus suggested that there must be a clear differentiation between the two. 10 Sleep bruxism is classified as a sleep-related movement disorder, and defined as an oral activity characterized by grinding or clenching of the teeth during sleep, usually associated with sleep arousal.…”
Section: Introductionmentioning
confidence: 99%
“…In a German study, researchers found strong associations of sleep bruxism with pain or tension in the muscles of the face upon awakening and articular noises and associations of awake bruxism with orofacial pain and articular noises 27 . In Brazil, a strong association has been shown among sleep bruxism, headache, facial pain, facial muscle fatigue and dental pain 28 because bruxists present with pain in the masticatory muscles as a result of prolonged contractions and hypertonic muscles.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess the frequency of awake bruxism subjects were asked to answer selected questions from the Oral Behaviors Checklist, a 21-item questionnaire regarding the activities of the masticatory system [10].…”
Section: Methodsmentioning
confidence: 99%
“…Awake bruxism is defined as the clenching of teeth and jaws during wakefulness, in comparison to sleep bruxism, which characterized by unconscious clenching or grinding of teeth during sleep [7]. Prevalence of bruxism in general population is not accurately estimated and varies from 15% to 36% across the studies, depending on the diagnostic method [8][9][10][11]. It is worth noting that bruxism is significantly more prevalent in patients with temporomandibular disorders in comparison to healthy subjects [12,13].…”
mentioning
confidence: 99%